Community Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 Disproportionately Affects the Latinx Population During Shelter-in-Place in San Francisco. (21st August 2020) - Chamie, Gabriel; Marquez, Carina; Crawford, Emily; Peng, James; Petersen, Maya; Schwab, Daniel; Schwab, Joshua; Martinez, Jackie; Jones, Diane; Black, Douglas; Gandhi, Monica; Kerkhoff, Andrew D; et al.
Abstract: Background: There is an urgent need to understand the dynamics and risk factors driving ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission during shelter-in-place mandates. Methods: We offered SARS-CoV-2 reverse-transcription polymerase chain reaction (PCR) and antibody (Abbott ARCHITECT IgG) testing, regardless of symptoms, to all residents (aged ≥4 years) and workers in a San Francisco census tract (population: 5174) at outdoor, community-mobilized events over 4 days. We estimated SARS-CoV-2 point prevalence (PCR positive) and cumulative incidence (antibody or PCR positive) in the census tract and evaluated risk factors for recent (PCR positive/antibody negative) vs prior infection (antibody positive/PCR negative). SARS-CoV-2 genome recovery and phylogenetics were used to measure viral strain diversity, establish viral lineages present, and estimate number of introductions. Results: We tested 3953 persons (40% Latinx; 41% White; 9% Asian/Pacific Islander; and 2% Black). Overall, 2.1% (83/3871) tested PCR positive: 95% were Latinx and 52% were asymptomatic when tested; 1.7% of census tract residents and 6.0% of workers (non–census tract residents) were PCR positive. Among 2598 tract residents, estimated point prevalence of PCR positives was 2.3% (95% confidence interval [CI], 1.2%–3.8%): 3.9% (95% CI, 2.0%–6.4%) among Latinx persons vs 0.2% (95% CI, .0–.4%) among non-Latinx persons. Estimated cumulative incidence among residents was 6.1% (95% CI, 4.0%–8.6%). Prior infections were 67% Latinx, 16% White, and 17% other ethnicities. Among recent infections, 96% were Latinx. Risk factors for recent infection were Latinx ethnicity, inability to shelter in place and maintain income, frontline service work, unemployment, and household income <$50 000/year. Five SARS-CoV-2 phylogenetic lineages were detected. Conclusions: SARS-CoV-2 infections from diverse lineages continued circulating among low-income, Latinx persons unable to work from home and maintain income during San Francisco's shelter-in-place ordinance.